2021
DOI: 10.1016/j.jinf.2021.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 vaccination program on seroprevalence in blood donors in England, 2021

Abstract: The COVID-19 vaccination programme commenced in England on 8 th December 2020 primarily based on age; by 7 th March 2021 approximately 93% of the English population aged 70+ years had received at least 1 dose of either the Pfizer BioNTech or AstraZeneca vaccines. Using a nucleoprotein assay that detects antibodies following natural infection only and a spike assay that detects infection and vaccine-induced responses, we aim to describe the impact of vaccination on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
6
11
0
Order By: Relevance
“…Our findings demonstrate both the feasibility and potential for broad application of using routinely collected blood samples to estimate community prevalence during a new outbreak. Now that a significant number of individuals have been vaccinated, it will be necessary to assay in parallel for antibodies to proteins in addition to spike ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate both the feasibility and potential for broad application of using routinely collected blood samples to estimate community prevalence during a new outbreak. Now that a significant number of individuals have been vaccinated, it will be necessary to assay in parallel for antibodies to proteins in addition to spike ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Whitaker et al ( 1 ) reported changes in SARS-CoV-2 seroprevalence in adults after introduction of a vaccination programme. Here we describe the impact of the delta wave and initiation of vaccination on seroprevalence in children.…”
mentioning
confidence: 99%
“…Serology assay selection for different requirements is complex ( 28 ). This initial program was principally focused on serosurveillance; further work is now under way at UKHSA Porton to determine antibody responses induced by vaccination ( 29 ), vaccine effectiveness ( 30 ), vaccine coverage, variant infection, and population spread ( 31 ), using a combination of serology assays targeting different antigens. With additional assays now available, we have expanded our assays to encompass those with improved sensitivity and specificity, with the capability to change rapidly, enabling better and more accurate analysis of the differing and refined responses to the SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%